The Problem of Existential Import in Metathetic Propositions: Qutb al-Din al-Tahtani contra Fakhr al-Din al-Razi - Yusuf Daşdemir (Nazariyat: Journal for the History of Islamic Philosophy and Sciences)
This paper addresses discussions in post-Avicennan Arabic logic on various characterizations of metathetic propositions and their status vis-à-vis the existential import condition by focusing on the arguments made by Fakhr al-Dīn al-Rāzī (d. 606/1210) and the counter-arguments by Quṭb al-Dīn al-Rāzī al-Taḥtānī (d. 766/1365), both of whom established their positions in a framework drawn by Avicenna (Ibn Sīnā, d. 428/1037), the most prominent figure in the tradition of classical Arabic logic. In his logic texts, Avicenna thoroughly discusses the problem of the existential import in metathetic propositions (ma‘dūla), and seems to have presumed the existential import to be a truth-condition for affirmative propositions, and therefore, for affirmative metathetic propositions as well. For Avicenna, in other words, an affirmative metathetic proposition presumes its subject-terms’s possibly existent referent(s). However, the theologian-philosopher Fakhr al-Dīn al-Rāzī, who lived about a century and half after Avicenna, criticized his views on metathetic propositions and their existential import among other things, thereby igniting a wave of debates in the tradition, in which Quṭb al-Dīn al-Taḥtānī participated in the following century. By studying this contained problem, this paper seeks to address a wider scholarly concern regarding the vitality of post-classical Arabic logic, and to establish that this period witnessed the flourishing of philosophical debate among Arabic logicians.